Teološki in bivanjski poudarki v nekaterih razpravah Vekoslava Grmiča - Lah, Avguštin (Časopis za zgodovino in narodopisje, 2023)
From the rich oeuvre (which could hardly be called systematic theology) of Vekoslav Grmič, whose disquisitions, both from a theoretical and a practical point of view, touch on many areas of personal, ecclesial, and social life, the works and topics selected are or will be those that highlight “new” or contemporary theological perspectives, views and reflections on essential and important existential topics such as man, faith, God, Jesus Christ, the Church, liberation, salvation and others. In the way a particular theme and its content/message is treated and perceived, its theological horizon of understanding and intervention for the all-round good of the individual and the community/religious community is revealed.
Keywords: Bog; božje ljudstvo; Cerkev; človek; Grmič, Vekoslav; krščanstvo; odrešenje; osvoboditev; teologija; teološka antropologija; vera